2011
DOI: 10.1038/nchembio.633
|View full text |Cite
|
Sign up to set email alerts
|

Twisted Schiff base intermediates and substrate locale revise transaldolase mechanism

Abstract: We examined the catalytic cycle of transaldolase (TAL) from Thermoplasma acidophilum by cryocrystallography and were able to structurally characterize--for the first time, to our knowledge--different genuine TAL reaction intermediates. These include the Schiff base adducts formed between the catalytic lysine and the donor ketose substrates fructose-6-phosphate and sedoheptulose-7-phosphate as well as the Michaelis complex with acceptor aldose erythrose-4-phosphate. These structural snapshots necessitate a revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 31 publications
3
72
0
Order By: Relevance
“…jannaschii has been characterized, and the crystal structure of TA from Tpl. acidophilum has been reported (127,(361)(362)(363)(364). However, in Mca.…”
Section: Fig 18mentioning
confidence: 98%
“…jannaschii has been characterized, and the crystal structure of TA from Tpl. acidophilum has been reported (127,(361)(362)(363)(364). However, in Mca.…”
Section: Fig 18mentioning
confidence: 98%
“…9 These properties are mainly due to the imine group present in Schiff bases, which could also be altered by varying the substituents in the molecules. [10][11][12] Furthermore, several studies have explored the properties of Schiff bases as catalysts, [13][14][15][16] uorescent materials, [17][18][19] electroluminescent materials, [20][21][22] etc. Since Schiff bases are known by their strong coordinative ability as a family of ligands, with the formation in most cases of 1 : 1 transition metal complexes, 23 they have been used to develop various chemosensors.…”
Section: Introductionmentioning
confidence: 99%
“…It remains unknown what if any the role of phosphate or phosphoryl radical is when it comes to DTT-fragment adduction at lysine N f H 3 þ groups. Interestingly, the Xray structure of a transaldolase reaction intermediate 43 shows similarities with our DTT-mediated reaction site.…”
Section: Discussionmentioning
confidence: 71%
“…Formation of Schiff bases at protein lysine N f groups is not unique. LehwessLitzmann et al 43 recently reported the X-ray structure of a transaldolase in which a Schiff base intermediate is observed at lysine K86. Our results from western blotting and MS fingerprinting also indicate that at least some serine and threonine residues, as well as possibly other oxygen-containing side chains, become phosphorylated during the DTT-mediated reaction.…”
Section: Discussionmentioning
confidence: 99%